Evaluation of Eosinophilic Myositis in a Bull: Histopathological and Immunohistochemical Findings - Milletsever, A; Ozmen, O (Journal of the Hellenic Veterinary Medical Society, 2025)
In this case report, histopathological and immunohistochemical findings of eosinophilic myositis (EM) observed in the gluteal muscles of a 15-month-old Holstein bull are presented. Macroscopically, multifocally distributed distinct gray-greenish demarcated foci were observed. Microscopic examinations revealed an inflammatory reaction with predominance of eosinophil granulocytes accompanied by mononuclear inflammatory cell infiltrations among myofibrils and increased connective tissue. Luna staining confirmed the presence of intracytoplasmic red granules in eosinophil leukocytes. Numerous remnants of sarcocyst cysts were found within the myofibers. Immunohistochemical examinations demonstrated increased expression of TNF-α, MMP-2, MMP-7, Cas-3, and IL-3. The findings of this study indicated the significant roles of cytokines, matrix metalloproteinases, and apoptosis in the development of eosinophilic myositis.